Penerapan Akuntansi Belanja Pegawai dan Belanja Barang di Masa Pandemi Covid-19 - Sri Annisa Sahuri; Agus Sunarya Sulaeman (Bongaya Journal for Research in Accounting (BJRA), 2021)
This research aims to determine the effect of the Covid-19 pandemic on the implementation of the accounting system for personnel expenditures and goods expenditures at KPPN Makassar II in 2020. This research is a qualitative research using auxilary data obtained from interviews and observations of the Financial Statements of KPPN Makassar II in 2020. The results of this study indicate that 1) The Covid-19 pandemic has an impact on the budget revision and the work from home work system at KPPN Makassar II but does not have a significant effect on the accounting treatment of personnel expenditures and goods expenditures at KPPN Makassar II application “SAKTI” has been implemented. so that the accounting treatment can be carried out in accordance with applicable regulations. 2) The accounting treatment of personnel expenditures and goods expenditures at KPPN Makassar II in the form of recognition, measurement, disclosure and presentation of personnel expenditures and goods expenditures is in accordance with applicable provisions, including Government Regulation Number 71 of 2010 concerning Government Accounting Standards, Regulation of the Minister of Finance Number 225 of 2019 concerning Central Government Accounting Policies, as well as related books and research.